Mapping of the main current international methodological trends in mathematics education and its teaching in the early years of Elementary Education (Research, Society and Development, 2023)
Mathematics represents one of the disciplines that Brazilian students, as indicated by data from the Basic Education Assessment System (SAEB), have significant difficulty in all stages of basic education. in Elementary School I is the responsibility of the generalist teacher licensed in Pedagogy. The central scope of this research was to map the main methodological tendencies used in the pedagogical work in the teaching and learning process of the thematic units established by the current National Common Curricular Base (BNCC) for this stage of basic education. The research is justified due to the unsatisfactory performance in Mathematics of students in this learning stage in the standardized large-scale assessment called Prova Brasil. The guiding question was to ask the subject teachers of the research if they realized that their methodological approaches used in the process of teaching and learning the teaching contents had implications for the students' learning? To answer this question, this research carried out in April 2022 resorted to research of a qualitative nature engendered in the procedures of phenomenological research. For data collection, semi-structured interviews were sought and, for analysis of the collected data, content analysis was carried out with a focus group of 28 teachers from the municipal public network of Greater Vitória -ES. The expressive results showed the prevalence of the methodological approach of Problem Solving, Critical Mathematics Education and Mathematical Games and revealed a lack of conceptual mastery over the other methodological approaches. Thus, it is concluded that the mathematical training of teachers in the early years has implications for the unsatisfactory results of Brazilian students in Mathematics.